The Decision to Wear a Face Mask as a Protective Behavioral Measure Against COVID-19: Survey Results From Greater Kampala Metropolitan Area, Uganda - Bukuluki, Paul M.; Kisaakye, Peter (Frontiers in Public Health, 2021)
The use of face masks is one of the behavioral measures used to prevent COVID-19 infection. Despite the positive contribution of face masks, there is uncertainty surrounding face mask wearing in low-income countries. Using data from 1,054 respondents in Greater Kampala Metropolitan area, we investigate the variation in face mask wearing inside and outside public spaces. Results indicate that more than three quarters of the respondents wore a face mask always outside public spaces and slightly more than half wore a face mask sometimes inside public spaces. Irrespective of location (inside or outside public spaces), respondents were more likely to wear facemasks sometimes or always to prevent COVID-19 infection. There is need to raise awareness about face mask wearing and its efficacy to prevent COVID-19 infection.